2013
DOI: 10.1002/elan.201300239
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Stripping Determination of Cadmium(II) and Lead(II) on Disposable Graphene Modified Screen‐Printed Electrode

Abstract: In the present work, a sensitive, facile and disposable sensing platform for trace analysis of heavy metal ions was developed at the Bi modified graphene-poly(sodium 4-styrenesulfonate) composite film screen printed electrode (GR/ PSS/Bi/SPE). The GR/PSS/Bi/SPE improved sensitivity and linearity due to the functionalization of graphene with negatively charged PSS providing more absorbing sites. The detection limit of the GR/PSS/Bi/SPE is found to be 0.042 mg L À1 for Cd 2 + and 0.089 mg L À1 for Pb 2 + with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This PPF material has also been considered in [140,141] to build in-situ or ex-situ Bi-modified pyrolyzed photoresist carbon electrodes for the determination of Ni(II) and Cr(VI) by AdSV using as complexing ligands DMG and pyrocatechol violet, respectively. Moreover, the use of graphene functionalized with negatively charged poly(sodium 4-styrene sulfonate) (PSS) improves the sensitivity and linearity of the analysis of Pb(II) and Cd(II) creating more adsorbing sites [142].…”
Section: Bismuth Electrodesmentioning
confidence: 99%
“…This PPF material has also been considered in [140,141] to build in-situ or ex-situ Bi-modified pyrolyzed photoresist carbon electrodes for the determination of Ni(II) and Cr(VI) by AdSV using as complexing ligands DMG and pyrocatechol violet, respectively. Moreover, the use of graphene functionalized with negatively charged poly(sodium 4-styrene sulfonate) (PSS) improves the sensitivity and linearity of the analysis of Pb(II) and Cd(II) creating more adsorbing sites [142].…”
Section: Bismuth Electrodesmentioning
confidence: 99%
“…[179] Chao et al used an in situ Bi film formed on graphite to sense Cd(II) and Pb(II), the linear response was in the range of 0.5 to 120 µg L −1 , with a detection limit of 0.042 ppb for Cd(II) and 0.089 ppb for Pb(II). [181] Fu et al reported a Bi film formed on multi-walled carbon nanotubes for sensing Zn(II), Cd(II), and Pb(II). The linear curves ranged from 0.5 to 100 µg L −1 with a detection limit of 0.3 ppb obtained for Zn(II), while Cd(II) ranged from 0.5 to 80 µg L −1 with a detection limit of 0.1 ppb, and Pb(II) ranged from 0.05 to 100 µg L −1 with a detection limit of 0.01 ppb.…”
Section: Mineral Water Samplesmentioning
confidence: 99%
“…In situ plated Bi film on Nafioncoated glassy carbon electrode [179] Pb(II): 8. Bi precursors electrode [180] Pb(II): 0.9 Cd(II): In situ plated Bi film on graphene screen-printed electrode [181] Pb(II): 0.089 Cd(II): 0.042 Water samples 0.5-120 µg L −1 for both DPASV, pH: 4.5, E d and t d : −1.3 V for 120 s, E step : 3 mV…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…They can also be easily modified with selected additives enabling them to display the beneficial properties of other materials. Graphitic materials such as carbon nanotubes (CNTs), graphene, graphene oxide (GO), carbon nanofibers (CNFs) and carbon nano-powders (CNPs) all have been successfully applied to SPEs, as modifications and/or inks for HM analysis in drinking water, [96][97][98][99][100][101] river-waters [102][103][104][105] and also food. [106][107][108] However, as suggested by Ping et al, the synthesis and application of some 2D-nanomaterials to large-scale production might be sometimes impractical.…”
Section: Graphitic Electrodesmentioning
confidence: 99%